Consumo de antimicrobianos en el servicio de 2c unidad de cuidados intensivos del hospital nacional edgardo rebagliati martins-essalud durante los meses de enero-junio 2008” - Junes Pérez, Tania Luz (2009)
This study evaluates the characteristics of antimicrobial consumption in the Intensive Care Unit (ICU) of the Hospital Nacional Edgardo Rebagliati Martins-Essalud during the months January to June 2008. A descriptive study, retrospective cross-utilization of medications, which included patients hospitalized in the Intensive Care Unit during the months of January to June 2008. Was used as the unit of measurement of defined daily dose (DDD), also recommended by the DURG, under this system for each ATM defines the average daily dose when used in its primary indication. We can see that in the period of study, imipenem / cilastatin shows 28.37% of total consumption which is equivalent to 2708 vials dispensed, followed by vancomycin with 16.19% equivalent to 1545 vials, while the medicine is the use of lower Cefepime with 2.76%. It was also noted that the drug is more DDD Imipenem / cilastatin 17.16 DDD/100camas-día, followed by 9.77 DDD/100camas-día vancomycin, ceftriaxone 8.31 DDD/100camas-día, while the drug is less DDD Meropenem 1.47 DDD/100camas-día. From the results we can conclude that the increased use of antimicrobial was Imipenem/cilastatina the antimicrobial 17.16 DDD/100camas-día and more expensive 45% of total expenditure in the period of time